Current Role of Chemotherapy in Metastatic Carcinoma Stomach- A Case Presentation and Review of Literature on Chemotherapy - Sahni, Manish; Rulaniya, Mukesh; Jasuja, Sandeep; Singh, Suresh (Asian Pacific Journal of Cancer Care, 2025)
Introduction and Importance: Systemic therapy can provide palliation, improved survival, and enhanced quality of life in patients with locally advanced or metastatic gastric cancer. First-line systemic therapy regimens with two cytotoxic drugs are preferred for patients with advanced disease because of their lower toxicity. The use of three cytotoxic drugs in a regimen should be reserved for medically fit patients with excellent performance status and easy access to frequent toxicity evaluations. But we are presenting a rare case report of 60 year old patient diagnosed with metastatic gastric carcinoma who showed long term complete response with single agent capecitabine based therapy which is a matter of contemplation in the current era. Case Presentation: 60 year old gentleman with ECOG 2 presented with complaints of loss of apetite and loss of weight from last 6 months.Clinical Findings and Investigations: Upper gastointestinal endoscopy of gastric mass was undertaken which revealed ulceroproliferative gastric growth and subsequently, gastic growth biopsy was done which on histopathology report revealed moderately differentiated gastric adenocarcinoma. Interventions and Outcome: For staging the disease, Whole body PET-CT scan was performed which showed FDG avid gastric lesion with multiple, bilobar liver metastasis and bulky retroperitoneal lymphadenopathy. All routine blood investigations were done simultaneously.Patient was counseled for ultrasound guided biopsy of liver lesions in Aug 2021. (Figure 1a, 1b, 1c) which showed metastatic deposits. We offered him to get IHC testing of biopsy sample for Her-2-neu, MSI testing and patient had Her2-neu negative disease. He was initiated on CAPOX dual agent regimen with tablet capecitabine 1000mg twice daily from day 1-14 cycled every 21 days and Injection oxaliplatin (Day 1) with dose of 130mg/m2 and repeated every 21 days for 8 cycles. He tolerated the chemotherapy well with improvement of general condition and showed partial response to treatment on whole body PET-CT scan (Figure 2) Case was discussed in multidisciplinary tumor board for further course of management and the plan to initiate tablet capecitabine monotherapy with 1000mg twice daily from day 1-14 cycled every 21 days was made as it was freely available in our tertiary cancer centre along with the nutritional support with enteral high protein diet. He was advised to remain on close follow up and after 1 month, he showed further improvement in symptoms with improved appetite and weight gain. Same cycles of capecitabine were continued and repeat whole body PET-CT scan was done at 6 months interval which showed no FDG avidity in the body. He is on same regimen till date and last repeat PET-CT scan was done in April 2024 which again showed complete response to treatment (Figure 3). Relevance and Impact: For patients with metastatic gastric carcinoma, performance status determines the type of therapy and treatment. Also IHC markers aids in the decision making in the type of therapy to be offered to the patient. Lastly, in low resource settings, metronomics in the form of capecitabine therapy assists in the control of this subset of the disease.